KONSELING GIZI PADA REMAJA OBESITAS - Lestantina, Afriska; Emy Yuliantini, Anang Wahyudi, (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Obesity is a condition of excessive weight due to excessive accumulation of fatin the body. The prevalence of obesity aged ≥ 15 years in 2015 in Bengkulu city is 308people (3.15%), the prevalence increases compared with the previous year. The purposeof this research is to know the influence of nutrition counseling to knowledge, energyintake, fat intake, and fiber intake in obese teenager at vocational high school 01bengkulu city in 2017. This research is pre-experiment research with pretest-postest onegroupdesign. The number of respondents obtained as many as 17 samples with SimpleRandom Sampling technique. Knowledge data were obtained from questionnairestatements, energy intake data, fat intake and fiber intake, obtained from 24-hour recallform. The data obtained were analyzed using the dependent T-test and Wilcoxon test. Theresults showed that there was influence of nutritional counseling to knowledge, there wasinfluence of nutritional counseling to energy intake, and there influence of nutritioncounseling to fat intake, whereas in fiber intake there was no effect of nutritioncounseling to fiber intake, mean post intervention was lower than pre intervention.Respondents need to pay attention and increase the consumption of foods high in fiberand lower consumption of foods high in energy and high fat and increase physicalactivity. As a follow up of nutrition counseling activities, schools are expected to providefacilities and infrastructure for adolescents to conduct nutritional counseling.